1992
DOI: 10.1007/bf00317150
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic comparisons of marine algal polyphenolics: evidence against a latitudinal trend

Abstract: Marine allelochemicals generally are present in greater quantity and diversity in tropical than in temperate regions. Marine algal polyphenolics have been reported as an apparent exception to this biogeographic trend, with literature values for phenolic concentrations significantly higher in temperate than in tropical brown algae. In contrast, our results, the first reported for Caribbean brown algae (orders Dictyotales and Fucales), show that many species have high phenolic levels. In addition, both our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 43 publications
8
74
1
1
Order By: Relevance
“…Our results suggest that one or several evolutionary forces act in a species-specific manner irrespective of the geographic area investigated. Similarly, the lack of a latitudinal trend in marine algal polyphenolics and the variability within species at both tropical and temperate regions suggest that other factors may play a more critical role within each geographic area (Targett et al 1992;Van Alstyne et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that one or several evolutionary forces act in a species-specific manner irrespective of the geographic area investigated. Similarly, the lack of a latitudinal trend in marine algal polyphenolics and the variability within species at both tropical and temperate regions suggest that other factors may play a more critical role within each geographic area (Targett et al 1992;Van Alstyne et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have not found support for a latitudinal gradient in chemical defenses (McCaffrey and Endean 1985;McClintock 1987;Steinberg and Paul 1990;Van Alstyne and Paul 1990; Van der Vyver et al 1990;Targett et al 1992;Van Alstyne et al 1999), which reinforces the need for direct tests of this hypothesis (Bolser and Hay 1996;Pennings et al 2001) and suggests that factors other than predation may act as evolutionary forces on these chemicals (Schmitt et al 1995;Bolser and Hay 1996;Becerro et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Kelps and fucoids, the main foundation species of temperate rocky reefs, commonly produce phlorotannins, some of which deter herbivory [55]. However, levels of phlorotannins in tropical and temperate brown algae vary substantially, with variation more a function of taxonomy and the specifics of geography than latitude per se [56]. Herbivores vary substantially in their response to phlorotannins, with some herbivores avoiding high concentrations [52], whereas others are unaffected [57].…”
Section: Mechanisms Facilitating the Tropicalization Of Temperate Sysmentioning
confidence: 99%
“…Phlorotannins are known only from brown algae (Phaeophyceae), where soluble phlorotannins can constitute up to 25% dry weight (e.g., Targett et al, 1992;Van Alstyne et al, 1999). They are suggested to have multiple ecological roles: some phlorotannins act as chemical defenses against herbivory (e.g., Steinberg, 1988;Targett and Arnold, 1998;Arnold and Targett, 2000;Pavia and Toth, 2000a) and as antifouling substances (Sieburth and Conover, 1965;Wikström and Pavia, 2004), although the evidence for this function is equivocal (Jennings and Steinberg, 1997).…”
Section: Introductionmentioning
confidence: 99%